The ‘Short Addiction Program’: experiences from an intervention by the correctional services in Norway - Hansen, Gunnar Vold (Criminal justice studies, 2017)
Do participants in a short term training program in prison find that it helps them to cope with their addiction better than before? This article explores the effects of a pilot project conducted in two Norwegian prisons. The study is based on interviews with 16 participants. The data show that the program increased inmates’ motivation and provided them with better tools to deal with their addiction. The conclusion is therefore that this kind of program could be the first step towards enabling prisoners with addictions to cope better with the challenges involved.